Pengaruh Pengalaman Kerja Dan Fasilitas Terhadap Kinerja Pegawai Pada Kantor Kecamatan Dolok Merawan Dengan Motivasi Kerja Sebagai Variabel Intervening - Suwadi Suwadi; Benhart Nainggolan; Muhammad Azwin Sinaga (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2025)
This study aims to determine the Effect of Work Experience and Facilities on Employee Performance at the Dolok Merawan District Office with Work Motivation as an Intervening Variable. The analysis method used in this study is to use an instrument test, namely validity and reliability tests. Classic assumption tests, namely normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis, determination coefficient analysis (R2), hypothesis tests, namely T tests and Path Analysis. The results of Smart PLS 3.0 in this study are that work experience affects work motivation, work facilities affect work motivation, work experience does not affect performance, work facilities affect performance, work motivation affects performance, Work Motivation can mediate the relationship between work experience does not affect employee performance, Work Motivation cannot mediate the relationship between work facilities and performance.